KAJIAN MAKNA SOSIAL-BUDAYARAMBU SOLO’ DALAM PEMBENTUKAN KARAKATER PESERTA DIDIK - Guntara, Fuad; Fatchan, Ach; Ruja, I Nyoman (FKIP Universitas Lampung, 2016)
The Study of Social-Cultural Meaning of Signs Solo’ in the Character Building of Students. The problems of young generationcharacter is the impact of globalization. It caused the need of character building education. Ceremony of solo’ signs that has social value and religus can be used as teaching material in character education. The purpose of this study was to determine the socio-cultural meanings of ceremony solo’ signs in Toraja. This study was a literature study by using descriptive analysis. The results are as follows: a). As a unifying container family; b). As a means to divide the inheritance; c). As a point of stating dignity; c). As a point of mutual cooperation and responsibility; d). As a container artistic development means; e). As a containers of donating. The ceremony of solo’ signs can be used as a source of learning for character education in accordance with the needs of learners characters desired by the Indonesian nation. Keywords:characters, signs solo’, learners DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601